Forward Modeling of Gravity Anomalies for Identification of Burried Cylindrical Body Using Radial Derivative - Zuhdi, Muhammad; Ayub, Syahrial; Syamsuddin, Syamsuddin (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2024)
Radial Derivative Forward Modeling of Gravity Anomalies for Identification of Cylindrical Geological Features. The gravity method is a geophysical method with exploration costs that are quite cheap compared to other geophysical methods. This method is based on the density contrast of the target body with the surrounding. The cylindrical body is one of the targets among various other geological features. This research was conducted to test the ability of radial derivatives of gravity anomalies for targets in the form of cylindrical body. Radial derivatives consist of a first derivative and a second derivative. Forward modeling of cylindrical geological features is carried out analytically and with finite elements. Both calculations were carried out with a computer program based on Matlab. The results show that there is no difference in results either analytically or finite element wise. This method has been proven to be able to provide clear boundary positions on cylindrical geological features.